PENGARUH PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DIMENSI MANDIRI TERHADAP KARAKTER DISIPLIN SISWA KELAS X SMA NEGERI 4 PEKANBARU - Nisa, Khairun; Hambali; Primahardani, Indra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted because it was motivated by the lack of students in having a disciplined character at school. The Influence of the Pancasila Student Profile Strengthening Project (P5) Independent Dimension is one of the activities implemented in schools which is to improve the disciplined character of these students. This study aims to analyze whether there is an influence of the Pancasila Student Profile Strengthening Project (P5) Independent Dimension on the Disciplined Character of Class X Students of State Senior High School 4 Pekanbaru. In this study, the highest indicator was obtained in the variable of the Pancasila student profile strengthening project (P5) independent dimension, namely the indicator of the reading corner design talent of the majority of respondents with a percentage of 62.23% indicating a very good category of reading corner design talent interest. Accumulatedly 99.9% of respondents have an interest in reading corner design talent in the very good and good categories. Based on these results, the interest in reading corner design talent is at a very good level. Based on the results of data analysis in this study, it was found that there was a positive and significant influence between the influence of the Pancasila Student Profile Strengthening Project (P5) Independent Dimension on the Disciplined Character of Class X.